Co-Constructing Knowledge Spheres in the Academy: Developing Frameworks and Tools for Advancing Publicly Engaged Scholarship. (April 2018) - Eatman, Timothy K.; Ivory, Gaelle; Saltmarsh, John; Middleton, Michael; Wittman, Amanda; Dolgon, Corey
Publicly engaged scholarship (PES) has emerged as a powerful force, yet institutional policies and cultures have often inhibited its acceptance in the academy. This article considers the benefits of PES for higher education as well as the obstacles to its enactment. It identifies the college level as a critical site for change and offers a rubric for institutional change agents to use to assess support for community engagement at the college level and identify avenues for further progress. The authors also grapple with tensions inherent in promoting PES at institutions that have historically served as agents of domination and oppression.